TERAPI HIPEROSMOLAR SEBAGAI TATA LAKSANA EDEMA SEREBRI PASCACEDERA KEPALA LAPORAN KASUS BERBASIS BUKTI - Ramdinal Aviesena Zairinal,* Irma Savitri Madjid,* Yetty Ramli,* Diatri Nari Lastri,* Adre Mayza* (NEURONA, 2018)
IS AN AGENT WIDELY USED TO TREAT HYPEROSMOLARITY IN CASES OF INCREASED INTRACRANIAL PRESSURE AFTER ACUTE TRAUMATIC BRAIN INJURY TBI HYPERTONIC SALINE IS AN ALTERNATIVE AGENT IN SUCH CASES BUT IS STILL NOT WELLRECOGNIZED IN DAILY PRACTICE THUS A LITERATURE SEARCHING WAS CONDUCTED TO SEE WHETHER MANNITOL IS MORE EFFECTIVE AND SAFER THAN HYPERTONIC SALINE IN REDUCING INTRACRANIAL PRESSURE IN PATIENTS WITH CEREBRAL EDEMA POST TBI